Stay-at-Home Orders, Social Distancing and Trust - Abel Brodeur; Idaliya Grigoryeva; Lamis Kattan (Global Labor Organization (GLO), 2021)
A better understanding of community response to government decisions is crucial for policy makers and health officials during the COVID-19 pandemic. In this study, we document the determinants of implementation and compliance with stay-at-home orders in the U.S., focusing on trust and social capital. Using cell phone data measuring changes in non-essential visitation and average distance traveled, we find that high-trust counties decrease their mobility significantly more than low-trust counties post stay-at-home order, with larger effects for more stringent orders. We also provide evidence that the estimated effect on post-order compliance is especially large for confidence in the press and governmental institutions, and relatively smaller for confidence in medicine and in science.
Keywords: H12; I12; I18; 330; COVID-19; stay-at-home orders; social distancing; trust